EVIDENCE-BASED PRACTICE IN THE CONTEXT OF THE FAMILY HEALTH SUPPORT CENTERS IN CHAPECÓ - Fátima Ferretti; Fabiana Romancini; Luana Roberta Schneider; Lucimare Ferraz (Universidade Federal do Paraná, 2018)
Objective: to analyze Evidence-Based Practice in the work of the professionals of the Family Health Support Center team. Method: descriptive study carried out in the municipality of Chapecó - Santa Catarina. The study population consisted of 28 professionals working in the centers in the year 2016. Data analysis was performed through descriptive statistics. Results: theprofessionals highlighted difficulties in converting knowledge needs into research questions, however, reported that they were able to collect scientific evidence and identify the main types and sources of information existing. Among the obstacles to the development of Evidence-Based Practice, they mentioned the high workload and lack of incentives from the managers. Conclusion: the professionals need to appropriate the elements of Evidence-Based Practice, helping the teams in the resolution of health problems.